1986
DOI: 10.1007/bf00710765
|View full text |Cite
|
Sign up to set email alerts
|

Pleomorphic adenomas, adenoid cystic carcinomas and adenolymphomas of salivary glands analysed by a monoclonal antibody against myoepithelial/basal cells

Abstract: Myoepithelial and basal cells were identified by a monoclonal antibody raised against keratin. This antibody (CK B1) which detects myoepithelial cells in normal salivary glands, labels spindle shaped and polygonal cells in pleomorphic adenomas. Most cells in adenoid cystic carcinomas and some basal cells in adenolymphomas were also positive for this antibody. The oncocytic epithelium of adenolymphoma was negative. An inverse reaction was seen with an antibody against cytokeratin 18. The antibody CK B1 seems to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
1

Year Published

1987
1987
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(12 citation statements)
references
References 35 publications
1
10
1
Order By: Relevance
“…Electron microscopic findings in salivary glands have indicated that striated ducts are composed of two cell types: light and dark (basal) cells, although some authors recognize three cell type: light, dark, and basal. Basal cells are also found in excretory ducts (5,18). The dark cells present in the basal region of the tumors might correspond to the cells indicating a positive reaction to PKKI and K8.12 in the present study.…”
Section: Discussionsupporting
confidence: 63%
“…Electron microscopic findings in salivary glands have indicated that striated ducts are composed of two cell types: light and dark (basal) cells, although some authors recognize three cell type: light, dark, and basal. Basal cells are also found in excretory ducts (5,18). The dark cells present in the basal region of the tumors might correspond to the cells indicating a positive reaction to PKKI and K8.12 in the present study.…”
Section: Discussionsupporting
confidence: 63%
“…Another possible progenitor cell as suggested reserve cell seems to be present in ductal segments (1,23); however, it is not known whether the ductal basal cell corresponds to the reserve cell. In order to evaluate these concepts, different monoclonal antibodies to keratin polypeptides were used to detect their localization specifically in intercalated, striated and excretory ducts and the ductal basal cells in human salivary glands (2,(7)(8)(9)12). In addition, the antibodies were used to compare the staining pattern of the different cellular types in pleomorphic adenomas.…”
mentioning
confidence: 99%
“…Immunohistochemical studies of keratins in pleomorphic adenomas have shown their consistent expression in the luminal tumor cells of tubuloductal structures, while there has been inconsistent and controversial expression in the modified myoepithelial cells (3-5, 7, 15, 17-20). By immunohistochemistry, intermediate sized filament proteins have been noted in adenoid cystic carcinomas (6,8) and sialocarcinomas (14,27).…”
mentioning
confidence: 99%
“…The particular presence of cytokeratin 8 and 18 was cited [Orito et al, 1989;Draeger et al, 1991]. Keratin 18 (CKB1) was also described in myoepithelial cells surrounding acini and in basal cells localized in the periphery of normal salivary gland ducts [Caselitz et al, 1986a, b]. Moreover, myoepithelial cells expressed actin [Bussolati et al, 1980;Palmer et al, 1985].…”
mentioning
confidence: 99%